Chronic Microglial Activation in the GFAP-IL6 Mouse Contributes to Age-Dependent Cerebellar Volume Loss and Impairment in Motor Function - Gyengesi, Erika; Rangel, Alejandra; Ullah, Faheem; Liang, Huazheng; Niedermayer, Garry; Asgarov, Rustam; Venigalla, Madhuri; Gunawardena, Dhanushka; Karl, Tim; Münch, Gerald (Frontiers in Neuroscience, 2019)
Chronic microglial activation is a prominent feature of many chronic neurodegenerative diseases, including Parkinson’s and Alzheimer’s disease. To investigate the effects of chronic microglial activation on cerebellar structure and motor function throughout the lifespan, the transgenic GFAP-IL6 mouse model was used. The aim of the study was to examine inflammatory markers and neuronal degeneration while simultaneously characterizing the motor performance of GFAP-IL6 mice at 3, 6, 14, and 24 months of age in comparison to WT (C57BL/6) mice. In respect to markers of neuroinflammation in the cerebellum, increased numbers of Iba1+ microglia were observed as early as at 3 months of age. In addition, TNF-α levels proved to be significantly higher in the GFAP-IL6 compared to WT mice at all time points. A difference in cerebellar volume between the GFAP-IL6 and WT mice was observed later in life, starting at 6 months and increasing to a loss of about 50% in aged (24 months old) GFAP-IL6 mice. Synaptic deficits were also assessed by using pre- (synaptophysin) and post-synaptic (PSD95) markers. While synaptophysin levels remained unchanged, PSD95 levels decreased in the aging GFAP-IL6 mice compared to their WT littermates from 14 months onward. To assess the effect of microglia activation and neurodegeneration on behavior, a variety of motor function tests, semi-quantitative cerebellar ataxia score, accelerod, beam walking, and open field tests were performed. An age-dependent difference between the genotypes was observed in many of the motor function tests. For example, reduced performance on the accelerod and higher ataxia scores were observed at 6 months of age, followed by the beam walking test showing differences at 14 months of age. In summary, this study constitutes a comprehensive, age-dependent examination of inflammatory, synaptic and neurodegenerative changes in the brains of GFAP-IL6 mice leading to a deterioration in motor performance. The results also indicate that early chronic microglia activation in the GFAP-IL6 mouse leads to observable cerebellar volume loss and motor deficits later in life.